Antyutopia — o gatunku, którego nie było - Krzysztof M. Maj (Zagadnienia Rodzajów Literackich)
The article collects a number of recent (and not-so-recent) arguments together against the common Polish usage of the term “anti-utopia” as synonymous with “dystopia” or, more often, as a name for a specifically defined genre which introduction requires producing confusing differentiations based on the degree of satire, criticism, or the lack of thereof in the fantastic extrapolation. The main thesis of the text comes from an observation that such scholarship seems to neglect a widely acknowledged discrepancy between utopia as a narrative or a world and utopianism as a transformative idea — which results in erroneous genological attribution of works famous inasmuch as George Orwell’s Nineteen Eighty-Four. To support the thesis, the article follows up with a series of etymological, philological, philosophical, and logical arguments in favour of using a term “dystopia” to denote any kind of narrative or world that deconstructs eutopian idealism, and reserving the predicate “anti-utopian” for a sociological critique of failed transformative efforts in society and philosophy.